Controversy Over The Rejection Of Interfaith Marriage Approval: Between The Circular Of The Supreme Court And The Population Administration Law In Indonesia - Ahmad Ridwan, Nur; Pujiyono, Pujiyono; Saptanti, Noor (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This article aims to review the tension between the Supreme Court Circular Number 2 of 2023 regarding Guidelines for Judges in Adjudicating Cases of Registration of Marriages between Different Religious and Belief Communities (SEMA) and Law Number 24 of 2013 concerning Amendments to Law Number 23 of 2006 concerning Population Administration (Adminduk Law), which creates a contradictory situationregarding interfaith marriages. Interfaith marriages havesparked controversy because they are not explicitly accommodated in Law Number 1 of 1974 concerning Marriage. As a result, parties involved in legal disputes face difficulties in navigatingthe applicable regulations. This article is a normative research with a conceptual approach. The research results indicate a conflict between SEMA and the Adminduk Law regarding interfaith marriages in Indonesia, creating inconsistency in legal regulations. SEMA, as a Supreme Court guideline, suggests rejection of approval, while the Adminduk Law allows it with court determination as a condition. Hans Kelsen's Stufen theory shows a legal hierarchy, with theAdminduk Law above SEMA. However, the inconsistency between the two poses challenges in achieving legal certainty and balancing diversity. The implementation of the Stufen Theory inIndonesia involves a hierarchy of regulations, with SEMA included as a type of regulation.Although SEMA applies in the judiciary, debates surrounding the rejection of interfaithmarriages highlight the inconsistency with the Adminduk Law.